Development of an Evidence-based Geotechnical Asset Management Policy for Network Rail, Great Britain. (2016) - Power, Christopher; Mian, Juliet; Spink, Tim; Abbott, Simon; Edwards, Michael
Abstract: Network Rail (NR) is the owner, operator and asset manager of the majority of the rail network of Great Britain, an infrastructure network totalling approximately 32, 000 kilometers of track. The challenge faced by Network Rail's earthworks asset managers is the aging infrastructure. Failures within the portfolio of nearly 200, 000 earthwork assets that NR manage are relatively common, particularly in periods of adverse or extreme weather. As a regulated industry, NR are constantly challenged to demonstrate continuous improvement to their management processes through each of their five year Control Periods (CPs). For the current CP5 (2014-2019), NR undertook a series of activities to develop an evidence-based asset management policy, the key steps of which are summarised in this paper, including: The development of a risk-based prioritisation matrix for all earthwork assets and determination of quantitative likelihood of earthwork failure The determination of quantitative consequences of earthwork failure The development of a series of earthwork intervention types, and the determination of the impact of these on the likelihood of earthwork failure The development and use of a strategic Whole Life Cost Decision Support Tool (DST) to model and optimise the CP5 earthworks policy and determination of key inputs to the DST, such as the assessed rate of asset portfolio deterioration. DST outputs were used to inform work bank development and Key Performance Indicators (KPIs) to measure the progress of the asset management policy through CP5 The paper briefly describes these activities and their results, and outlines how the policy has been embedded into the NR business. It describes how the policy has been used to secure funding for CP5, and how the work banks prepared against this funding have undergone assurance to determine alignment to the policy. Finally, the paper touches on future developments.